2015
DOI: 10.1523/jneurosci.2484-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Deprivation Disrupts Homeostatic Regeneration of Newly Generated Olfactory Sensory Neurons after Injury in Adult Mice

Abstract: Although it is well known that injury induces the generation of a substantial number of new olfactory sensory neurons (OSNs) in the adult olfactory epithelium (OE), it is not well understood whether olfactory sensory input influences the survival and maturation of these injury-induced OSNs in adults. Here, we investigated whether olfactory sensory deprivation affected the dynamic incorporation of newly generated OSNs 3, 7, 14, and 28 d after injury in adult mice. Mice were unilaterally deprived of olfactory se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 59 publications
9
100
0
Order By: Relevance
“…Although it remains to be determined how rapidly OSN presynaptic terminal turnover is affected by naris occlusion, it is clear that the marked reduction in OSN presynaptic terminal turnover elicited by 3 weeks of naris occlusion was not a consequence of changes at the level of the olfactory epithelium, as we found no effect of naris occlusion on numbers of immature or mature OSNs, or proliferating or apoptotic cells. This is in agreement with a recent study, which found no change in epithelium thickness, total number of OSNs or number of OMP+ OSNs at time points 3–28 days post naris occlusion in adult mice 46 . Hence, a transient effect of naris occlusion on OSN survival is also unlikely.…”
Section: Discussionsupporting
confidence: 94%
“…Although it remains to be determined how rapidly OSN presynaptic terminal turnover is affected by naris occlusion, it is clear that the marked reduction in OSN presynaptic terminal turnover elicited by 3 weeks of naris occlusion was not a consequence of changes at the level of the olfactory epithelium, as we found no effect of naris occlusion on numbers of immature or mature OSNs, or proliferating or apoptotic cells. This is in agreement with a recent study, which found no change in epithelium thickness, total number of OSNs or number of OMP+ OSNs at time points 3–28 days post naris occlusion in adult mice 46 . Hence, a transient effect of naris occlusion on OSN survival is also unlikely.…”
Section: Discussionsupporting
confidence: 94%
“…The equilibrium between OSN survival and apoptosis is possibly regulated by odorant-stimulated neural activity and sensory experience (Zhao et al, 2013; Cadiou et al, 2014; Kikuta et al, 2015). Sensory input plays a critical role in the survival of OSNs during postnatal MOE development (Farbman et al, 1988; Stahl et al, 1990; Brunjes, 1994; Coppola et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Olfactory dysfunction is a frequent complaint in CRS patients and significantly affects their quality of life [26]. The etiology results from a long-term inflammatory process that causes respiratory metaplasia, airway obstruction and incomplete ORN regeneration [26,27]. Although CS interferes with the formation of tight junction and impedes mucociliary differentiation of RECs, it is a promising agent to facilitate the ORN differentiation of ONCs.…”
Section: Discussionmentioning
confidence: 99%